Implementasi Nilai dan Etika Pekerja Sosial melalui Pendampingan Relawan Sosial bagi Lansia - Faizal Efendi; Renda Nur Rofiah (Fakultas Dakwah UIN Kiai Haji Achmad Siddiq Jember, 2022)
The meaning of social work is clearly stated in Law No.11 of 2019 which emphasizes that a social worker is someone who works, whether working for a government or private institution that already has the potential for social work itself. Social Work is work that can be done by everyone. As long as there are objects or materials, and a willingness to be able to help others in solving the social problems faced, then this can already be said to be a social worker. PP number 43 of 2004 Article 1 paragraph 4 and 5, the condition of the elderly in Indonesia can be divided into two, namely potential elderly and non-potential elderly. Potential elderly are elderly who have the ability to meet their needs, such as by working and not depending on others. The method used in this study is a descriptive type of research with a qualitative approach by describing the implementation of the values and ethics of social workers through social volunteer assistance for the elderly at LKSLU. Sunan Drajat Banyuwangi in overcoming the problems faced by the elderly. . The results of this study indicate that the implementation of the values and ethics of social workers through the assistance of social volunteers at the social welfare institute for the elderly Sunan Drajat Banyuwangi, namely; 1). Humanitarian principles, 2). Service 3). Help, 4). Concerned with human relations. However, in the process, it cannot be denied that in practice not everything can run according to the expected program, in the sense that there are ethical dilemmas that are experienced in handling such as; the skills of social assistants or volunteers themselves, handling clients, elderly people such as small children, and the lack of budget funds.